Epikarst zone of a karst aquifer – its characteristics and importance in karst hydrogeology - Branka Trček (Geologija, 2002)
The karst aquifer’s epikarst zone is a subject of the research. It is an important part of the aquifer, particularly from a hydrodynamic point of view. The study background is a hypothesis supposing that an important part of a karst aquifer’s recharge arrives, rapidlyand in concentrated form, from the epikarst zone. The hypothesis is argued on basis of results of the study referring to the karst aquifer in the catchment area of Hubelj spring and results of many previous researches from all over the world. The synthesis of all dataproduces information on main characteristics of the epikarst zone, its role in aquifer’s hydraulic behaviour and the resulting consequences.